Relationship between circulating tumour cell count and prognosis following chemotherapy in patients with advanced non‐small‐cell lung cancer. Issue 3 (10th December 2015) - Zhang, Zixuan; Xiao, Yi; Zhao, Jing; Chen, Minjiang; Xu, Yan; Zhong, Wei; Xing, Jia; Wang, Mengzhao
Abstract: Background and objective: This study investigated whether circulating tumour cells (CTC) are detectable in patients with non‐small cell lung cancer (NSCLC) and whether CTC count could provide prognostic information or serve as an indicator of patient response to chemotherapy. Methods: We enrolled 46 patients with newly diagnosed or recurrent NSCLC. CTC were measured at baseline in all patients and in 23 patients, CTC were also measured before every chemotherapy cycle. The relationship between CTC count and tumour size was analysed. Results: CTC were present in 40 patients (87%); among them, 29 (63%) had a CTC count of ≥3 cells/3.2 mL, 17 (37%) had a CTC count of ≥5 cells/3.2 mL and 7 (15.2%) had a CTC count of ≥8 cells/3.2 mL. The median progression‐free survival (PFS) and overall survival (OS) were 7.3 months and 16 months, respectively. A CTC count of more than eight prior to chemotherapy was a strong predictor of reduced PFS ( P = 0.018) and OS ( P = 0.026). A multivariate analysis indicated that baseline CTC count was an independent negative prognostic factor for survival. However, no correlation was observed between CTC count and tumour size after two chemotherapy cycles, its relationship with chemotherapy response still needs to be defined. Conclusion: Baseline CTC count is an independent negative prognostic factor for NSCLC; The relationship of CTC and survival after chemotherapy still needs to be defined. Abstract : We measured circulating tumour cells (CTC) at baseline and at every chemotherapy cycle in patients with non‐small cell lung cancer (NSCLC). We found baseline CTC count can serve as prognostic marker for NSCLC; however, its relationship with chemotherapy response still needs to be defined.